1997
DOI: 10.1159/000196708
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of a Double-Blind, Randomized Trial of Inhaled Steroids in a Patient with Lung Transplant Bronchiolitis Obliterans

Abstract: Lung transplant bronchiolitis obliterans syndrome (BOS) is the most significant long-term cause of morbidity and mortality after lung transplantation. Although augmented immunosuppression is used by most centers, reported on treatment to reverse BOS are largely anecdotal. We performed a double-blind, randomized, controlled trial (RCT) with ten treatment pairs of 2 weeks duration each comparing inhaled fluticasone propionate (2 × 1,000 μg/day) with placebo in a patient with BOS grade 2 who previously showed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In contrast, corticosteroids or immunosuppressants, rather than macrolide, may be beneficial to patients with OB [21,22,23,24]. However, Gerhardt et al [25] have recently reported the efficacy of oral maintenance therapy with azithromycin for OB.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, corticosteroids or immunosuppressants, rather than macrolide, may be beneficial to patients with OB [21,22,23,24]. However, Gerhardt et al [25] have recently reported the efficacy of oral maintenance therapy with azithromycin for OB.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few reports on the addition of inhaled corticosteroids to the standard immunosuppressive regimen in the management of BO following lung transplantation [88][89][90][91][92]. These reports do not show clinically significant benefit in the prevention or treatment of BO.…”
Section: Managementmentioning
confidence: 99%
“…Treatment of patients with BO/BOS rarely reverses the lung dysfunction. Several therapies have been attempted; a few have resulted in stabilization of the patient's pulmonary status but treatment is generally disappointing [3,4,6,8,9,14,[16][17][18][19]22]. However, even when attempts are made to reverse or stabilize the patient's pulmonary status, progression of the chronic rejection process frequently occurs.…”
mentioning
confidence: 99%